Kajian Hukum Pertanggungjawaban Korporasi Yang Melakukan Pencemaran Lingkungan - Khairunnisa Fahriati; Nurul Listiyani; Iwan Riswandie (Scholar Center, 2021)
Environmental pollution can occur due to activities carried out by corporations. The increasing number of development activities has an impact on the environment, pollution and environmental damage. The impact of environmental pollution is very dangerous for the lives of living things and the comfort of the environment in the future. The state of Indonesia has prepared a regulation in an effort to protect the environment as in law number 32 of 2009 conceming prorection and management of the environment. With the issuance of law number 11 of 2020 concerning job creation using the omnibus law model, the main theme of this law is to create jobs and investment. To make it easier to achieve this goal, a simplification of a permit was carried out. Therefore, law number 32 of 2009 conceming prorection and management was also affected by to permits and several articles that were changed, replaced, and abolished. This research was conducted to find out how the legal regulation of environmental pollution in law number 11 of 2020 concerning job creation and how the form of corporate responsibility as perpetrators of environmental pollution according to law number 11 of 2020 concerning job creation. The mothod used in this study is normative. The source of the legal material used is primary secondary legal material. The results of this study discuss the simplification of licensing and revisions to a number of articles in law number 32 of 2009 concerning environmental protection and management due to the issuance of law number 11 of 2020 concerning job creation and shifting criminal sanctions into administrative sanctions in the job creation act is one the weaknesses in environmental law enforcement against corporations that are perpetrators of pollution environment.